(untitled) (CIPEEX, 2025)
This study investigates the relationship between spirituality, work, and human dignity, considering religion as a starting point for reflection and analysis. The objective is to understand how spirituality, understood as the capacity to connect with the Divine and to recognize shared values, can influence professional life by attributing deeper meaning and promoting emancipation. The research draws upon three key works: Mere Christianity by C.S. Lewis, The Protestant Ethic and the Spirit of Capitalism by Max Weber, and The Book That Made Your World by Vishal Mangalwadi. Lewis highlights the transformative role of faith and moral values in shaping human character and social relations. Weber examines how Protestant ethics, particularly Calvinism, influenced the rise of modern capitalism and the perception of work as a vocation. Mangalwadi emphasizes the biblical perspective of labor as a divine calling that enhances dignity, responsibility, and social progress. Methodologically, the study combined bibliographic research with a qualitative interview conducted with a professional engaged in the intersection of spirituality and work. Results indicate that spirituality positively impacts the workplace by fostering relationships based on love, justice, and empathy, while also reinforcing the understanding of work as a path to both personal and social transformation. The findings suggest that spirituality is not limited to religious rituals but extends to everyday relationships, offering a foundation for human dignity and emancipation in contemporary society. In conclusion, the study demonstrates that integrating spirituality into work contributes to ethical development, strengthens social cohesion, and provides meaning beyond economic necessity, transforming labor into a vocation that advances both individual and collective well-being.